The species composition of rotifers in three hydroelectric reservoirs of western highlands, Central Vietnam - Hung, Duong Quang; Truong, Phan Nhat; Minh, Vo Van; Anh, Tran Nguyen Quynh; Mau, Trinh Dang (Academia Journal of Biology, 2021)
The rotifer fauna in three hydroelectric reservoirs of western highlands, central Vietnam were studied. Among a total of 63 identified species and subspecies, beloging to 23 genera in 15 families, Brachionidae was the most diverse family with 15 taxa recorded (23.81%) followed by Lecanidae (14 taxa, 22.22%), and Synchaetidae (8 taxa, 12.7%). Species accumulation curve and species richness estimators suggested a relatively high level of biodiversity of rotifera assemblages in the studied area. Besides, results on species composition of rotifera community in this study were compared to those of other freshwater bodies in Vietnam using Jaccard similarity index. In particular, the highest similarity was found between reservoirs in western highlands and Phu Ninh lake, Quang Nam Province while the largest difference in species composition was observed between western highlands and Bau Thiem lake, Thua Thien Hue Province.